2006
DOI: 10.1111/j.1365-263x.2006.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of rubber dam usage amongst specialists in paediatric dentistry practising within the UK

Abstract: Current BSPD guidelines recommend rubber dam usage for many restorative procedures; however, it would appear that there is wide variability in the application, as well as under-use, of rubber dam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 14 publications
4
25
0
11
Order By: Relevance
“…Previous studies have reported under-usage of RD, [6][7][8][9][10][11][12][13][14][15] a similar finding to this study. RD has been available since 1864 and is considered an ideal device for tooth isolation in restorative dentistry.…”
Section: Jofrsupporting
confidence: 82%
See 3 more Smart Citations
“…Previous studies have reported under-usage of RD, [6][7][8][9][10][11][12][13][14][15] a similar finding to this study. RD has been available since 1864 and is considered an ideal device for tooth isolation in restorative dentistry.…”
Section: Jofrsupporting
confidence: 82%
“…The reported use of RD for OD procedures is lower, as compared to endodontic therapy 11 and composite is the most commonly reported restoration to be placed under RD. 6,15 In the present study, dentists in government sector used RD more often than those working in the private sector. This is in accordance with Udoye and Zafarzadeh 7 who reported a similar finding in Nigeria.…”
Section: Jofrmentioning
confidence: 75%
See 2 more Smart Citations
“…Para a confecção de restaurações de resina composta a literatura afirma que o isolamento absoluto é a escolha mais eficaz para o controle da contaminação do ambiente bucal 18 . Porém, há vários estudos que equiparam o isolamento relativo, quando bem realizado, ao isolamento absoluto como forma de manutenção de um campo operatório e até mesmo no desempenho clínico de restaurações de resina composta 19,20 . Assim, no presente caso, o isolamento relativo modificado, com roletes de algodão e expansor de boca e gazes, foi escolhido por ser uma região de fácil controle de umidade do meio bucal.…”
Section: Discussionunclassified